2009
DOI: 10.1038/aja.2008.31
|View full text |Cite
|
Sign up to set email alerts
|

18, X, Y aneuploidies and transmission electron microscopy studies in spermatozoa from five carriers of different reciprocal translocations

Abstract: We analysed ejaculated spermatozoa from five infertile men with different balanced reciprocal translocations to contribute to the study of meiotic segregation of chromosomes 18, X and Y and also to evaluate sperm morphology by transmission electron microscopy (TEM) analysis. Conventional lymphocyte karyotype analyses highlighted dif ferent reciprocal balanced translocations: t(12;13), t(4;9), t(X;8), t(8;10) and t(3;16). Semen analysis was performed by light and TEM. Fluorescence in situ hybridization was perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 22 publications
1
11
2
Order By: Relevance
“…All the balanced translocation rates were in accordance with literature values (i.e. a mean aneuploidy rate close to 50 % for translocation segregation and around 2 % for the ICE [13,23,28]). Due to the small sample size for ICSI and IMSI selected spermatozoa, no statistical analyses were performed.…”
Section: Discussionsupporting
confidence: 88%
“…All the balanced translocation rates were in accordance with literature values (i.e. a mean aneuploidy rate close to 50 % for translocation segregation and around 2 % for the ICE [13,23,28]). Due to the small sample size for ICSI and IMSI selected spermatozoa, no statistical analyses were performed.…”
Section: Discussionsupporting
confidence: 88%
“…Sex chromosome disomy frequencies estimated for the present study were higher than previously reported ranges among men using manual counting (XX, 0.03-0.37; YY, 0.04-0.21; XY, 0.06-0.42, sex chromosome disomy 0.27) (Egozcue et al, 1997;Templado et al, 2005Templado et al, , 2011. In a study of fertility clinic patients who were known reciprocal translocation carriers, XY disomy was as high as 4.1% (Moretti et al, 2009). Additionally, in a recent studies of sperm disomy among andrology clinic patients using automated methods, Tempest et al (2010) and McAuliffe et al (2012) also reported higher total sex-chromosome disomy (averaging between 1.3% and 1.90% total disomy) compared with previously reported ranges (Egozcue et al, 1997).…”
Section: Tablecontrasting
confidence: 76%
“…In a study of fertility clinic patients who were known reciprocal translocation carriers, XY disomy was as high as 4.1% (Moretti et al 2009). Because we did not routinely perform karyotypes, we do not know the prevalence of underlying reproductive conditions such as Robertsonian translocations in our clinic sample.…”
Section: Discussionmentioning
confidence: 99%